A 12-Month Follow-up of the "Le U" for Lumbar Interspinous Fixation: Do Obese Patients Benefit More?. Issue 3 (August 2015) - Lemcke, Johannes; Störtländer, Björn; Al-Zain, Ferass; Winklmann, Katharina; Danne, Marco; Meier, Ullrich
Abstract : Background: Posterior lumbar decompression and interspinous fixation is a surgical technique used in the treatment of the spinal stenosis, degenerative spondylolisthesis, and facet joint arthosis complex. Interspinous fixation implants are less invasive than posterior lumbar internal fixator and therefore, are well suited for use as an implant in cases of low-grade spondylolisthesis. The aim of this study was to examine the clinical and radiographic outcome of patients treated with lumbar decompression and interspinous fixation. Methods: Forty-two patients treated by lumbar decompression and interspinous fixation using the "Le U" and cared for in a specialized urban hospital for degenerative spinal stenosis, together with low-grade spondylolisthesis and facet joint arthrosis, were reviewed. The follow-up rate was 88% (42 of 48 patients) at 1 year. The patients were assessed clinically and radiographically. Results: At 6 months of follow-up, there were 20/42 patients (48%) with an excellent clinical outcome in terms of back pain and the sciatia. Twelve months after surgery, 15/42 patients (36%) showed an excellent outcome in relation to back pain and 21/42 patients (50%) showed an excellent outcome in relation to sciatia. The interspinous implant was dislocated in one of the 42 patients. No differences were found between female and male patients, but there were differences between patients with a normal weight and overweight patients. Conclusions: The study demonstrated that lumbar decompression and interspinous fixation with the "Le U" in patients with degenerative spinal stenosis, low-grade spondylolisthesis, and facet joint arthosis results in excellent and good clinical outcomes. Although all patients showed a significant improvement in relation to back pain and sciatia, overweight and obese patients showed a tendency to benefit more than those with a normal weight.